Microscopic Identification and Quality Assurance of Zandu Nityam Churna - Rana, C S; Kathait, A S; Joshi, M C; Rai, R K (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Constipation is a common digestive disorder with multiple underlying causes. Zandu Nityam Churna is a classical Ayurvedic formulation known for its laxative properties and pleasant taste, which relief in general constipation. This formulation contains key herbal ingredients such as Svarnapatri, Erand, Haritaki, Baheda, Amla, Yashtimadhu, and Saunf. These ingredients have been examined through powder microscopy for authentication and validation of the finished product. Despite the availability of advanced analytical tools, microscopic evaluation remains one of the simplest and most effective techniques for the identification of crude herbal drugs. Various published literature have also supported microscopic authentication and quality control of herbal churna formulations. Materials and Methods: The powdered sample was soaked in water to soften the materials and then centrifuged for 5 min for the sedimentation. The suspended portion of the sample was carefully transferred to clean Petri dish and mounted with glycerin and then analyzed under a Labomed Microscope to identify the specific cellular structures, starch grains, and crystals at different magnifications. Results and Discussion: Zandu Nityam Churna microscopy revealed the presence of stomata and trichomes in the leaf fragments of Svarnapatri (Cassia angustifolia Vahl.), oil globules of Erand (Ricinus communis L.), epicarp cells and brachysclereids types stone cells of Amla (Phyllanthus emblica L.), osteosclereids types stone cells and parenchymatous tissue of Haritaki (Terminalia chebula Reitz.), spiral vessels and stone cells of Baheda (Terminalia bellerica Gaertn. Roxb.), xylary vessels and stone cells of Yastimadhu (Glycyrrhiza glabra L.), and aleurone grains and mericarp cells of the fruits of Saunf (Foeniculum vulgare Mill.). Conclusion: Powder microscopy serves as a vital tool in the authentication of powdered formulations. This technique is mainly important in the context of herbal medicines, where accurate identification of plant materials is essential. Employing such investigative methods can enhance consumer confidence in the authenticity and reliability of Churna formulations.